Telomere protein complexes and their role in lymphoid malignancies - Panero, Julieta (2017)
Telomeres are highly regulated and dynamic complexes that protect the genomic DNA and prevent the end of linear chromosomes from being misrecognized as a broken DNA. Due to the end replication problem, telomeres of somatic cells shorten with each cell division, inducing cell senescence. Telomerase is a reverse transcriptase capable of compensating telomere attrition by adding telomere repeats to the ends of chromosomes. Human telomeres are associated with the shelterin complex which consists of six telomere-associated proteins that specifically bind to telomeric DNA. Alterations or removal of individual shelterin components would lead to telomere uncapping and telomere dysfunction, resulting in cellular senescence and transformation to a malignant state. Another complex of multifunctional proteins, named non-shelterin complex, is thought to prevent telomere degradation and facilitate telomerase-based telomere elongation. As telomerase is highly expressed in most human tumor cells, it is considered an attractive target for new therapeutic strategies. In this review, we will summarize the characteristics of telomeres and telomerase in lymphoid malignancies and discuss the role of telomere-associated proteins in these entities.